A setup to study atomic state population dynamics and optical polarization at CRYRING@ESR - Mohr, Konstantin Thilo; Sánchez, R.; Nörtershäuser, W.; Geithner, W.; Andelkovic, Z.; Hannen, V.; Hanu, E.-O.; Herfurth, F.; Heß, R.; Horst, M.; Imgram, P.; König, K.; et al. (Journal of Instrumentation, 2025)
We present a recently established setup for laser spectroscopy at CRYRINGESR at the GSI Helmholtz Centre for Heavy Ion Research. Here, laser spectroscopy can be performed on stored and cooled ion bunches and coasting beams. First spectra of 24,25Mg+ ions are presented that were recorded by classical Doppler-limited fluorescence spectroscopy as well as Λ-spectroscopy using counter- and copropagating laser beams that are Doppler-shifted by several nm.
Gesehen am 03.11.2025